ACCUMULATION OF BIOLOGICALLY ACTIVE COMPOUNDS IN ELEUTHERO (ELEUTHEROCOCCUS SENTICOSUS /RUPR. ET MAXIM. / MAXIM) GROWN IN POLAND - Baczek, K.; Weglarz, Z.; Przyby, J. I. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Eleuthero (Siberian ginseng) is a slender shrub, usually 2-3 m high. It is native to northeastern Asia. Underground parts of this plant (rhizomes with roots) are used as a medicinal raw material and are classified as a drug with adaptogenic activity. Eleutherosides are regarded as main active compounds of eleuthero. Taking into consideration the interest of the Polish herbal industry in standardized eleuthero raw material, in the Department of Vegetable and Medicinal Plants of Warsaw University of Life Sciences – SGGW the studies on cultivation and raw material quality of eleuthero were undertaken. In the experiment, two-, three- and four-year-old plants grown under reduced light accessibility were investigated. In late autumn rhizomes with roots and bark from woody stems were harvested. The content of eleutherosides B and E and phenolic acids in the raw materials were determined by HPLC. The total content of eleutherosides B and E in the dried rhizomes with roots exceeded considerably the content of these compounds required by the British Pharmacopoeia (80 mg/100 g). In the raw material of two-, three- and four-year-old plants it amounted to 104.7, 167.4 and 292.4 mg/100 g, respectively. The content of eleutherosides in the bark of woody stems was almost twice as high as the content of these compounds in the rhizomes with roots. Both rhizomes with roots and bark of woody stems were characterised by high content of phenolic acids, especially chlorogenic acid (849.8 and 421.0 mg/100g, respectively).